A web-based system for automating the assessment question setting and assessment activities for Primary School mathematics - Neo, Kai Lun (2014)
This project was carried out in order to develop an online assessment system that is highly flexible and capable of generating infinite questions. The initial focus of this project is on Singapore’s education system, the national Primary School Leaving Examination (PSLE). However, this system is developed with the possibility of expansion to other standards, such as GCE ‘N’, ‘O’ and ‘A’ Level, and possibly even other education systems. This system also generates questions in the form of open-ended word problem questions. Besides examining the student's capability of understanding mathematical concepts, the system can also test the student’s ability to discover the word problem in a given question and form a solution to identify problem. Online assessment systems usually require a databank for the questions. However, modeling the questions dynamically into templates would allow smaller databases, as many unique questions can be generated from a single template. There will also be no concern that the same question would be repeated. This will make the system more flexible, as well as support the possibility of expansion. This is because the system will be able to generate the questions regardless of standard or topic, as long the question type is modeled into a template correctly. Hence, the method of modeling is used in this project to generate questions and providing individual analysis progress report.